Rhizobacterial volatile organic compounds: Implications for agricultural ecosystems' nutrient cycling and soil health - Faryal Babar Baloch; Nan Zeng; Haiyang Gong; Zhiyong Zhang; Ning Zhang; Sadia Babar Baloch; Shahzaib Ali; Bingxue Li (Heliyon)
Plant growth-promoting rhizobacteria (PGPR) have emerged as key players in sustainable agriculture due to their ability to enhance plant growth, nutrient uptake, and disease resistance. A significant aspect of PGPR is the emission of volatile organic compounds (VOCs), which serve as signaling molecules that influence various physiological processes in plants. This review article explores the complex interactions between rhizobacterial VOCs and soil health, focusing particularly on their role in nutrient cycling within agricultural ecosystems. By investigating the mechanism of production and release of VOCs by rhizobacteria, along with impacts on soil properties and microbial communities. We aim to highlight the potential of rhizobacterial volatile organic compounds (VOCs) for sustainable agricultural management. Additionally, we discuss the role of rhizobacterial VOCs in promoting root growth, nutrient uptake, and enhancing nutrient cycling processes. By providing insights into these mechanisms, this review offers tailored strategies for exploring the potential of rhizobacterial VOCs to optimize nutrient availability, enhance soil fertility, and address environmental challenges in agriculture. Exploring the potential of rhizobacterial VOCs presents an opportunity to establish sustainable and resilient agricultural systems that significantly enhance global food security and promote environmental stewardship.